PERBEDAAN FREKUENSI KOLONISASI COMMUNITY ACQUIREDMETHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS PADA NARES ANTERIOR PASIEN HUMAN IMMUNODEFICIENCY VIRUS DENGAN KADAR SEL T CD4+ < 200 SEL/Î¼L DAN â¥ 200 SEL/Î¼L - , dr. Yuliana Laksmini; , dr. Fajar Waskito, MKes, Sp.KK(K), ([Yogyakarta] : Universitas Gadjah Mada, 2012)
CA-MRSA infection is important health problem, especially in HIV-infected patients. Colonization of CA-MRSA in the anterior nares is a predisposing factor for infection with identical strain. In HIV-infected patients, CD4+ T cell number is the best indicator of relative stage of the disease. In HIV-infected patients, there were deficiency of innate and adaptive immune system, especially occurred when the number of CD4+ T cell falls < 200/Âµl. The aim of this study was to compare the occurence of anterior nares CA- MRSA colonization between HIV-infected patients with CD4+T cell< 200/Âµl and â¥ 200/Âµl. Design of this study is cross-sectional. Specimen of nasal swab taken from HIV patients in outpatient clinic. Identification was performed by inoculation on blood agar at 37Â°C for 18-24 hours and Gram staining to identify Staphylococcus sp. Staphylase test was done to identify S.aureus. Finally, identification of MRSA was performed with cefoxitin disk on Mueller Hinton Agar using Kirby-Bauer method. Result : ninety-four participants included on this study, consist of 69,1% men and 30,9% women, mean of age was 34,1 Â± 7,8 years old. Colonization of CA-MRSA was found in 14 (14,9%) patients. The occurrence of nares anteriores CA-MRSA colonization between HIV-infected patients with CD4+T cell< 200/Âµl and â¥ 200/Âµl was not statistically different(p=0,082). Colonization of CA-MRSA was associated with receiving cotrimoxsazole [p 0,026, CI 0,811(0,726-0,905)]. Conclusion : The occurence of nares anteriores CA-MRSA colonization in our HIV population was high and it didnât differ significantly between HIV-infected patients with CD4+T cell< 200/Âµl and â¥ 200/Âµl.